Preparation method of heat storage material with high temperature resistance, low expansion, high heat storage and high resistance
By coating magnesia particles with organic matter to form a gradient structure, the problem of traditional materials being prone to deformation and breakdown at high temperatures has been solved, achieving efficient thermal energy storage and long-life thermal storage performance.
Patent Information
- Application Number
- CN202511086410.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-05
- Publication Date
- 2025-11-18
AI Technical Summary
Existing solid thermal storage materials suffer from problems such as high thermal expansion coefficient, easy deformation and cracking under high temperature conditions, and insufficient resistance to high voltage current breakdown, resulting in low thermal storage efficiency and short service life.
Magnesia particles are used as aggregate, and a gradient structure of magnesia particles-ring pores-spinel/cordierite reaction layer-mullite is formed through a coating process. Combined with high-alumina bauxite and kaolinite, a mullite matrix is formed, which reduces the coefficient of thermal expansion and improves the electrical resistance.
It achieves high density, high specific heat capacity, low expansion coefficient and high resistance. The material has good stability at high temperature, strong puncture resistance and long service life.
Smart Images

Figure CN120965350A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid electric thermal energy storage boilers, and particularly relates to a method for preparing a high-temperature resistant, low-expansion, high-heat-storage, and high-resistance thermal energy storage material, which is applicable to electric thermal boilers. Background Technology
[0002] Solid-state thermal energy storage technology is a highly efficient, environmentally friendly, and safe thermal energy storage technology that converts fluctuating electrical energy such as off-peak electricity, wind power, and photovoltaic power into thermal energy for storage. It has broad development prospects in areas such as district heating system renovation, peak-valley power regulation, and industrial heat production. Currently, solid-state thermal energy storage electric boilers suffer from low thermal energy storage efficiency in actual operation, severely limiting their development. Therefore, researching and developing high-quality thermal energy storage materials is crucial. Existing solid-state thermal energy storage materials mainly include magnesia bricks, clay bricks, and ceramics.
[0003] Traditional clay thermal storage bricks have a low coefficient of thermal expansion and good volume stability under rapid heating and cooling, exhibiting good performance. However, they have low density, low specific heat capacity, and poor heat storage capacity. In addition, their resistance to high-voltage current breakdown is insufficient, posing a risk of high-voltage current breakdown under high-temperature service conditions. Traditional MgO thermal storage bricks have the characteristics of high bulk density, high specific heat capacity, strong heat storage capacity, and strong resistance to high-voltage current breakdown. However, their significant drawbacks include a large coefficient of thermal expansion at high temperatures, poor volume stability under rapid heating and cooling, susceptibility to deformation and cracking, and susceptibility to moisture absorption, resulting in a short service life. Summary of the Invention
[0004] To address the above problems, the purpose of this invention is to provide a method for preparing a heat storage material that is resistant to high temperatures, has low expansion, high heat storage capacity, and high resistance.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a high-temperature resistant, low-expansion, high-heat-storage, and high-resistance thermal storage material is disclosed. The thermal storage material is designed based on the material's microstructure. Magnesia particles with a particle size ≥1mm are selected as aggregate, and an organic coating process is used to coat the magnesia particles. Then, 30-50 parts of coated magnesia particles, 40-50 parts of high-alumina bauxite, 4-6 parts of binding clay, 2-3 parts of binder, and 3-6 parts of aqueous solution are mixed. After bundling the mixture, a blank is formed using a machine pressing process. The thermal storage material is then obtained after high-temperature heat treatment. The prepared thermal storage material exhibits a gradient structure of magnesia particles-ring pores-spinel / cordierite reaction layer-mullite, achieving a synergistic effect of low thermal expansion coefficient, high heat storage capacity, and high hot-state resistance. The chemical composition of the prepared thermal storage material is: MgO 10-50%, Al2O3 50-80%, SiO2 10-40%, and a small amount of impurities. Magnesia particles are used as aggregate to achieve high heat storage, high electrical resistance, and high puncture resistance in the material. The magnesia particles are coated with organic matter, and the annular pores formed after the organic matter is burned off during heat treatment can effectively buffer the thermal expansion of magnesia under high temperature conditions and reduce the coefficient of thermal expansion of the material. Magnesia particles with a particle size greater than 1 mm are introduced to reduce the specific surface area of magnesia and the amount of interfacial reaction between magnesia and alumina and SiO2, thereby reducing the amount of low-melting-point substances such as cordierite and ensuring that the high-temperature performance of the material is not reduced.
[0006] High-alumina bauxite and kaolin are used as fine powders to form a mullite matrix in situ, giving the material an overall low coefficient of thermal expansion of mullite-cordierite.
[0007] The heat storage material has a porosity of 18%-23% and a density of 2.4-2.6 g / cm³. 3 Specific heat capacity greater than 1072 J / (kg*K); heat storage density greater than 2.734 J / cm³ 3 *K; Pressure resistance reaches 50-90 MPa; Hot resistance at 1000℃ is not less than 17.477*10 3 The service temperature shall not be lower than 1350℃; the strength retention rate shall not be lower than 80% after 5 cycles of water cooling at 1000℃.
[0008] The organic compound is one of amino resin, phenolic resin, or styrene-acrylic emulsion.
[0009] The particle size of the magnesia sand is 1-3 mm.
[0010] The high-alumina bauxite has a particle size of 0-1 mm and a mass fraction of 10-15 parts; or a particle size of 0-75 μm and a mass fraction of 30-35 parts.
[0011] The bonding clay mentioned is one of kaolin or Guangxi white clay. The binder is one of the following: aluminum dihydrogen phosphate, pulp waste liquor, and dextrin. The binding time shall not be less than 6 hours; the heat treatment temperature shall be 1350℃-1430℃.
[0012] This invention provides a method for preparing a heat storage material for electric boilers that is resistant to high temperatures, low expansion, high heat storage, high resistance, and high voltage breakdown. Based on the microstructure design of the material, this invention selects magnesia particles as aggregate to prepare a composite heat storage material with mullite coating. The introduction of magnesia aggregate achieves high heat storage, high resistance, and high breakdown resistance. The organic coating of the magnesia particles, after heat treatment, forms annular pores that effectively buffer the thermal expansion of magnesia under high-temperature conditions, reducing the material's coefficient of thermal expansion. The introduction of magnesia particles with a diameter greater than 1 mm reduces the specific surface area of magnesia and the amount of interfacial reaction between magnesia and alumina / SiO2, decreasing the formation of low-melting-point substances such as cordierite, ensuring that the material's high-temperature performance is not reduced. High-alumina bauxite and kaolin are used as fine powders to form a mullite matrix in situ, resulting in a material exhibiting a low coefficient of thermal expansion of mullite-cordierite. Through the design of the material's microstructure, a gradient structure of magnesia particles-ring pores-spinel / cordierite reaction layer-mullite is formed, achieving a synergistic effect of low thermal expansion coefficient, high heat storage capacity, and high thermal resistance.
[0013] The beneficial effects of this invention are as follows: 1. High density (density ≥ 2.51 / (g·cm-3)), high specific heat capacity, and high heat storage density (heat storage density ≥ 2690.72 / (kJ·m-3)), the material has strong heat storage capacity.
[0014] 2. High hot resistance (1000℃ hot resistance ≥17.477*103), strong resistance to high voltage current breakdown.
[0015] 3. Low expansion (thermal expansion coefficient ≤ 5.0 × 10-6 / ℃-1), good thermal shock stability, and long material service life (strength retention rate reaches more than 80% after 5 cycles of rapid cooling and heating). Attached Figure Description
[0016] Figure 1 A photograph of the heat storage material prepared in Example 1.
[0017] Figure 2 , Figure 3 The gradient structure of the heat storage material prepared in Example 1 is magnesia particles-ring pores-spinel / cordierite reaction layer-mullite.
[0018] Table 1 shows the performance indicators of the heat storage material prepared in Example 1. Detailed Implementation
[0019] The present invention will be described in detail with reference to the accompanying drawings and specific embodiments: like Figure 1 , Figure 2 , Figure 3As shown, a heat storage material for electric boilers is characterized by high temperature resistance, low expansion, high heat storage capacity, high resistance, and resistance to high-voltage current breakdown. The chemical composition of the material is: MgO 10-50%, Al2O3 50-80%, SiO2 10-40%, and impurities. The microstructure of the material exhibits a gradient structure of magnesia particles, ring-shaped coated pores, a spinel / cordierite reaction layer, and mullite. The porosity of the material is 18%-23%, the density is 2.4-2.7 g / cm³, the specific heat capacity is greater than 1072 J / (kg*K), the heat storage density is greater than 2.734 J / cm³*K, the compressive strength reaches 50-90 MPa, and the hot resistivity at 1000℃ is not less than 17.477*10⁻⁶. 3 The service temperature shall not be lower than 1400℃.
[0020] The present invention also provides a method for preparing the above-mentioned heat storage material, which includes coating magnesium sand particles with a particle size ≥1mm with organic matter using a coating process, then mixing 30-50 parts by weight of coated magnesium sand, 40-60 parts of high-alumina bauxite, 4-6 parts of kaolin, 2-3 parts of binder, and 3-6 parts of aqueous solution, bundling the mixture into shape, and finally preparing the heat storage material by high-temperature heat treatment.
[0021] The present invention will be described in detail below through examples. Example 1:
[0022] In this embodiment, 30 parts by weight of magnesia particles with a particle size of 1-3 mm are added to a mixer, and an amino resin solution is added for wet mixing to ensure that the surface of the magnesia particles is fully wetted and coated with a layer of amino resin. Then, 20 parts by weight of high-alumina bauxite particles with a particle size of 1-3 mm; 10 parts by weight of high-alumina bauxite particles with a particle size of 0-1 mm; 34 parts by weight of high-alumina bauxite fine powder with a particle size ≤0.074 mm; and 6 parts by weight of kaolin fine powder with a particle size ≤0.074 mm are weighed and premixed. The premixed material was added to a mixer, and then 6 parts of pulp solution were added for mixing. The pulp solution contained a pulp and water ratio of 1:1. After mixing, the material was bundled for 6 hours and formed into a blank using a machine pressing process. The blank was dried at 110℃ for 24 hours. The dried blank was placed in a kiln and heated to 300℃ at a rate of 1℃ / min and held for 2 hours. Then, the temperature was increased from 300℃ to 1350℃ at a rate of 1.5℃ / min and held for 2 hours. A heat storage material with high temperature resistance, low expansion, high heat storage, high resistance, and resistance to high voltage and current breakdown was obtained. The performance indicators are shown in Table 1. Example 2:
[0023] In this embodiment, 35 parts by weight of magnesia particles with a particle size of 1-3 mm are added to a mixer, and an amino resin solution is added for wet mixing to ensure that the surface of the magnesia particles is fully wetted and coated with a layer of amino resin. Then, 15 parts by weight of high-alumina bauxite particles with a particle size of 1-3 mm; 10 parts by weight of high-alumina bauxite particles with a particle size of 0-1 mm; 34 parts by weight of high-alumina bauxite fine powder with a particle size ≤0.074 mm; and 6 parts by weight of kaolin fine powder with a particle size ≤0.074 mm are weighed and premixed. The premixed material was added to a mixer, and then 6 parts of pulp solution were added and mixed. The pulp solution contained a pulp and water ratio of 1:1. After mixing, the material was bundled for 6 hours and formed into a blank using a machine pressing process. The blank was dried at 110℃ for 24 hours. The dried blank was placed in a kiln and heated to 300℃ at a rate of 1℃ / min and held for 2 hours. Then, the temperature was increased from 300℃ to 1350℃ at a rate of 1.5℃ / min and held for 2 hours to obtain a heat storage material with high temperature resistance, low expansion, high heat storage, high resistance, and resistance to high voltage breakdown. Example 3:
[0024] In this embodiment, 40 parts by weight of magnesia particles with a particle size of 1-3 mm are added to a mixer, and an amino resin solution is added for wet mixing to ensure that the surface of the magnesia particles is fully wetted and coated with a layer of amino resin. Then, 10 parts by weight of high-alumina bauxite particles with a particle size of 1-3 mm; 10 parts by weight of high-alumina bauxite particles with a particle size of 0-1 mm; 34 parts by weight of high-alumina bauxite fine powder with a particle size ≤0.074 mm; and 6 parts by weight of kaolin fine powder with a particle size ≤0.074 mm are weighed and premixed. The premixed material was added to a mixer, and then 6 parts of pulp solution were added and mixed. The pulp solution contained a pulp and water ratio of 1:1. After mixing, the material was bundled for 6 hours and formed into a blank using a machine pressing process. The blank was dried at 110℃ for 24 hours. The dried blank was placed in a kiln and heated to 300℃ at a rate of 1℃ / min and held for 2 hours. Then, the temperature was increased from 300℃ to 1350℃ at a rate of 1.5℃ / min and held for 2 hours to obtain a heat storage material with high temperature resistance, low expansion, high heat storage, high resistance, and resistance to high voltage breakdown. Example 4:
[0025] In this embodiment, 45 parts by weight of magnesia particles with a particle size of 1-3 mm are added to a mixer, and an amino resin solution is added for wet mixing to ensure that the surface of the magnesia particles is fully wetted and coated with a layer of amino resin. Then, 5 parts by weight of high-alumina bauxite particles with a particle size of 1-3 mm; 10 parts by weight of high-alumina bauxite particles with a particle size of 0-1 mm; 34 parts by weight of high-alumina bauxite fine powder with a particle size ≤0.074 mm; and 6 parts by weight of kaolin fine powder with a particle size ≤0.074 mm are weighed and premixed. The premixed material is added to the mixer, and then 6 parts by weight of pulp solution are added for mixing. The pulp solution has a pulp-to-water ratio of 1:1. After mixing, the material is bundled for 6 hours and formed into a blank using a machine pressing process. The material is dried at 110℃ for 24 hours. The dried green body is then placed in a kiln and heated to 300℃ at a rate of 1℃ / min and held for 2 hours. Then, the temperature is increased from 300℃ to 1350℃ at a rate of 1.5℃ / min and held for 2 hours to obtain a heat storage material that is resistant to high temperature, low expansion, high heat storage, high resistance, and high voltage breakdown.
[0026] Table 1 shows the performance indicators of the heat storage material prepared in Example 1.
Claims
1. A method for preparing a high-temperature resistant, low-expansion, high-heat-storage, and high-resistance heat storage material, characterized in that: The thermal storage material is designed based on the microstructure of the material. Magnesia particles with a particle size ≥1mm are selected as aggregates and coated with organic matter using a coating process. Then, 30-50 parts of coated magnesia particles, 40-50 parts of high-alumina bauxite, 4-6 parts of binding clay, 2-3 parts of binder, and 3-6 parts of aqueous solution are mixed. After the mixed material is bundled, it is formed into a blank by machine pressing. After high-temperature heat treatment, the thermal storage material is obtained. The obtained thermal storage material exhibits a gradient structure of magnesia particles-ring pores-spinel / cordierite reaction layer-mullite, achieving a synergistic effect of low thermal expansion coefficient, high thermal storage capacity, and high thermal resistance. The chemical composition of the prepared thermal storage material is: MgO 10~50%, Al2O3 50-80%, SiO2 10-40%, and a small amount of impurities.
2. The preparation method of a high-temperature resistant, low-expansion, high-heat-storage, and high-resistance heat storage material as described in claim 1, characterized in that: The heat storage material has a porosity of 18%-23% and a density of 2.4-2.6 g / cm³. 3 Specific heat capacity greater than 1072 J / (kg*K); heat storage density greater than 2.734 J / cm³ 3 *K; Pressure resistance reaches 50-90 MPa; Hot resistance at 1000℃ is not less than 17.477*10 3 The service temperature shall not be lower than 1350℃; the strength retention rate shall not be lower than 80% after 5 cycles of water cooling at 1000℃.
3. The preparation method of a high-temperature resistant, low-expansion, high-heat-storage, and high-resistance heat storage material as described in claim 1, characterized in that: The organic compound is one of amino resin, phenolic resin, or styrene-acrylic emulsion.
4. The method for preparing a high-temperature resistant, low-expansion, high-heat-storage, and high-resistance heat storage material as described in claim 1, characterized in that: The particle size of the magnesia sand is 1-3 mm.
5. The method for preparing a high-temperature resistant, low-expansion, high-heat-storage, and high-resistance heat storage material as described in claim 1, characterized in that: The high-alumina bauxite has a particle size of 0-1 mm and a mass fraction of 10-15 parts; or a particle size of 0-75 μm and a mass fraction of 30-35 parts.
6. The method for preparing a high-temperature resistant, low-expansion, high-heat-storage, and high-resistance heat storage material as described in claim 1, characterized in that: The bonding clay is one of kaolin or Guangxi white clay.
7. The method for preparing a high-temperature resistant, low-expansion, high-heat-storage, and high-resistance heat storage material as described in claim 1, characterized in that: The binding time shall not be less than 6 hours; the heat treatment temperature shall be 1350℃-1430℃.
8. The method for preparing a high-temperature resistant, low-expansion, high-heat-storage, and high-resistance heat storage material as described in claim 1, characterized in that: The impurities mentioned are K2O, Na2O, CaO, and Fe2O3.
Citation Information
Patent Citations
Preparation method of hercynite-series refractory material for cement kiln high-temperature zone
CN110590354A
Organic-inorganic composite thermal insulation material and preparation method thereof
CN114773742A
Polymer-encapsulated expansion agent for well cementing
EP3228608A1
